Tax Amnesty in Law Number 11 of 2016 Seen from The Perspective of Fiqh Al-Darībah (Taxation in Islam) - Wigati, Sri; Sholihuddin, Muh; Jazil, Saiful (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
This research aims to elaborate on tax amnesty according to the provision set forth in Law Number 11 of 2016 seen from the perspective of fiqh al-ḍarībah or Islamic taxation. This library research studied secondary data sourced from books, journals, or other references. All the data were analyzed based on a content analysis technique. The research results reveal that tax amnesty is a breakthrough established by the government to expedite economic growth and restructure the economy by transferring assets, considering that this measure can increase domestic liquidity, increase exchange rate, decrease interest rate, and increase investment. Tax amnesty is part of the taxation reform paving into more just taxation and a more valid, comprehensive, and integrated taxation database. The values obtained from this tax collection should contribute to national development. From the perspective of fiqh al-ḍarībah, tax amnesty is within the study of mu'āmalah ijtihādiyyah, where the government is authorized to make laws concerning taxation and adheres to the principles of welfare and justice for citizens. The government is also responsible to decide the amounts of taxes to be paid by taxpayers. Ulama, however, suggested that there should not be any likelihood that taxation is perceived as a burden by people and that the collected taxes are intended for immoral conduct. Moreover, taxation is decided in deliberation. If all these requirements are not fulfilled, taxes collected may represent sinful conduct or injustice.